Efficacy of Amphotericine B drug Against Promastigote and Axenic Amastigote of Leishmania tropica in Vitro - M. Abbas, Zhor; H. Zghair, Khawla (Iraqi Journal of Science, 2023)
Leishmania are protozoan parasites belonging to the family Trypanosomatidae that cause high morbidity and mortality levels with a wide spectrum of clinical syndrome. This study aimed to investigate the effect of liposomal amphotericin B (AmBisome) drug on promastigote and axenic amastigote stages of Leishmania tropica. From the 20 isolates of cutaneous leishmaniasis collected from patients attended to the AL-Karama Teaching Hospital in Baghdad during the period from October 2013 until February 2014, only three isolates successfully transformed to motile promastigote stage in the culture media. The most active one is included in this study. Different concentrations of liposomal amphotericin B (AmBisome) and pentostam Sb (V) drugs were investigated against Leishmania tropica promastigote and axenic amastigote. The IC50 values of SbV and AmBisome drugs on promastigote were 5.42 mg/ml and 2.14 μg/ml, respectively, while they were 0.88μg/ml and 0.75 μg/ml respectively, for axenic amastigote. The present study concluded that axenic amastigote was more sensitive than promastigote against both drugs, and AmBisome drug showed high effectiveness against both stages with low concentrations in comparison with pentostam.